2018
DOI: 10.1049/iet-bmt.2018.5074
|View full text |Cite
|
Sign up to set email alerts
|

Low‐quality fingerprint classification using deep neural network

Abstract: Fingerprint recognition systems mainly use minutiae points information. As shown in many previous research works, fingerprint images do not always have good quality to be used by automatic fingerprint recognition systems. To tackle this challenge, in this work, the authors are focusing on very low-quality fingerprint images, which contain several well-known distortions such as dryness, wetness, physical damage, presence of dots, and blurriness. They develop an efficient, with high accuracy, deep neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Most current approaches extract minutiae from fingerprint images and perform fingerprint matching based on the number of corresponding minutiae pairings [3,8,33,35]. Shell et al [33],questions regarding human fingerprint orientation and found that expertise in fingerprints increases the accuracy of marked-up orientation field, which is a characteristic feature.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Most current approaches extract minutiae from fingerprint images and perform fingerprint matching based on the number of corresponding minutiae pairings [3,8,33,35]. Shell et al [33],questions regarding human fingerprint orientation and found that expertise in fingerprints increases the accuracy of marked-up orientation field, which is a characteristic feature.…”
Section: Related Workmentioning
confidence: 99%
“…Although fingerprints theoretically can identify people with high accuracy, the real-world performance of the systems highly depends on the condition of the finger's surface, i.e., humidity, dust, temperature, etc., which can drop the identification accuracy [35]. Features such as OF, which is representing the trend of the ridge flow of fingerprint [16,42], are usually used for low-quality fingerprint segmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this recognition approach is widely recognized for its authentication precision and the likelihood that the same fingerprint occurring in two persons is minimal. All said and done, there are other instances where the system fails to recognize some fingerprints due to the possibility that the fingerprint reader may lose its sensitivity with time, or a user's fingerprint might be damaged [8]. ese problems lend us to two main errors in recognition, thus Type-I and Type-II errors.…”
Section: Introductionmentioning
confidence: 99%
“…Deep neural networks, due to their high accuracy, are widely used in many of the computer vision applications such as emotion recognition [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], biometric recognition [ 17 , 18 , 19 , 20 ], personality analysis [ 21 , 22 ], and activity analysis [ 5 , 23 , 24 ]. Depending on the nature of the data, different structures can be used [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%